Olimp N. Căciulă. "Euharistia ca jertfă" ["Eucharist as a Sacrifice"]. Translated by Ioan Ică sr. Sibiu: Deisis, 2016, 410 p. - BUT-CĂPUȘAN, Dacian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
Under the auspices of the prestigious Deisis Publishing House in Sibiu, the doctoral thesis of Ph. Fr. Olimp N. Căciula was published and promoted to the Faculty of Theology of the National and Capodistrian University of Athens in 1931, being translated for the first time in Romanian by Fr. Prof. Ioan Ica Sr. who also signs the foreword entitled: Olimp Căciulă and the remarkable theological generation of Great Romania. The book has nine chapters grouped in two parts, each with several subdivisions: Part I: About the sacrifice in general (I. Religion and sacrifice, II. The origin of the sacrifice, III. The Being of the sacrifice, IV. A brief look at the Jewish sacrifices and Part II: About the Eucharistic sacrifice in particular, V. The teaching of the Orthodox Church on the Eucharistic sacrifice – the acceptance of the Eucharist as a sacrifice, VI. The teachings of the Protestant Church on the Eucharistic sacrifice – the denial of the Eucharist as a sacrifice, VII. The Eucharistic Sacrifice in the Tradition of the First Centuries of the Church, VIII. The Eucharistic Sacrifice according to Holy Scripture, IX The Being of the Eucharist as a Sacrifice).